THE ANALYSIS OF REGULATORY REQUIREMENTS FOR DETERMINING THE EMISSION OF POLLUTANTS FROM EXHAUST GASES FROM ENGINES INTERNAL COMBUSTION DIESEL LOCOMOTIVES (Transport systems and technologies, 2018)
In rail transport, the main sources of air pollution are diesel engines (internal combustion piston engine) locomotives. In the field of railway transport in Ukrainian there are several of standards norms that regulate emission of pollutants with exhaust gases diesel locomotive engines, the requirements for gas analyzers to monitor emissions from transport and others. In many countries, the norm of pollutant emissions with exhaust gases from engine of vehicles have undergone significant changes, so we must perform a comparison require ments of regulations regarding the norms methods of determining emissions of pollutants with exhaust gases from diesel locomotive engines. In the article analyzed and considered the requirements of the standards of different countries for regulation and methods of determining emissions of pollutants exhaust gases from diesel locomotive engines. Standards was compared on the following criteria: emission standards, modes and cycles of testing, measuring of exhaust for smoke and determination of particulate emissions, the error of measurement parameters, requirements for gas analyzers. Based on the analysis found large differences in standards of pollutant emissions, unlike acceptable error during testing, and test cycle modes, different approaches to the calculation and technical requirements for equipment test stands. This in turn leads to finding ways to bring the standards and methods of calculation to common standards.
Keywords: Internal combustion engines, pollutant emissions, exhaust gases, test modes